Construction of clay brickwall / Amirul Abd Gani - Abd Gani, Amirul (2021)
Brickwall is a very important thing to elaborate, therefore this report will discuss about clay brickwall for the building envelope. This report was conducted for the building envelope at new Hospital Parit Buntar Perak construction. The objective of this report is to gain knowledge and information about clay brickwall and how far it fulfills the requirements in the guideline. It will focus on the method construction of clay brickwall and the equipments and materials used to construct a clay brickwall. This report also will discuss about the advantages and disadvantages of clay brickwall. Every objective will achieve with the own observation and interview with the worker of this construction site.